A low-density formaldehyde-free particleboard and its preparation process

By modifying biomass lignin, liquid polyester polyol is prepared and reacting with isocyanate to prepare polyurethane adhesive, which solves the problem of insufficient mechanical strength and water resistance of particleboards, and realizes formaldehyde-free and environmentally friendly lightweight particleboard preparation .

CN118456589BActive Publication Date: 2025-02-07GUANGXI FUSUI RUNHONG WOOD IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410564984.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-02-07
Estimated Expiration
2044-05-09

AI Technical Summary

Technical Problem

The existing particle board has shortcomings in terms of mechanical strength and water resistance, and the adhesive used for glue application contains formaldehyde, which poses a threat to the environment and human health.

Method used

The lignin from biomass was modified to prepare liquid polyester polyols and used to prepare the core layer of the particle board. Polyurethane adhesive was prepared by reacting with isocyanate to form light particle board without formaldehyde.

Benefits of technology

It realizes lightweight particle board without formaldehyde, has good mechanical properties and water resistance, and the preparation process is free of organic solvents, which is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004828933130000071
    Figure BDA0004828933130000071
Patent Text Reader

Abstract

The present invention belongs to the technical field of particleboard preparation, and provides a low-density formaldehyde-free particleboard and a preparation process thereof. The preparation process comprises the following steps: preparation of lignin-based liquid polyester polyol; modulation of sizing solution; shavings sizing and paving; pressing and molding. Among them, the lignin-based liquid polyester polyol is prepared by using lignin, chloroacetic acid, mixed small molecule diols and methyl allyl alcohol; the sizing solution utilizes lignin-based liquid polyester polyol instead of polyols from petroleum sources, adds G-15 liquid tackifying resin, vinyl tris (β-methoxyethoxy) silane, foaming agent, catalyst and isocyanate, foams and reacts during pre-pressing and pressurizing, produces a strong bonding effect, and prepares a particleboard with excellent performance and no formaldehyde. The present invention obtains a formaldehyde-free lightweight particleboard with good mechanical properties, and the preparation process is free of organic solvents and is very environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of particleboard preparation, and in particular to a low-density formaldehyde-free particleboard and a preparation process thereof. Background Art

[0002] Particleboard is a man-made board made through processes such as particle preparation, drying and sorting, gluing, paving, pre-pressing, and hot pressing. Compared with solid wood boards, particleboard can reduce the amount of wood used, and the resulting product has a smooth surface, realistic texture, uniform bulk density, and small thickness error. Therefore, it has been widely used in furniture, home furnishings, decoration, packaging and other fields.

[0003] Particleboard can be divided into three types according to product density: low-density, medium-density, and high-density. The amount of wood used increases in turn, and low-density particleboard can save more wood resources. With the shortage of wood resources and the growing demand for raw materials, low-density and lightweight have become an important development trend of particleboard products. The current disadvantage of low-density particleboard products is that due to the large number of gaps between the particles, the bonding between the structural units is weak, and a uniform continuous phase structure cannot be formed, resulting in a significant decrease in the mechanical strength and water resistance of the board. The use of adhesive foaming can fill the gaps between the particles, promote the bonding between the particles, and improve the mechanical properties and water resistance of the board.

[0004] At present, the adhesives used for particleboard gluing are mostly urea-based adhesives, mainly including urea-formaldehyde, phenol-formaldehyde, and melamine-modified formaldehyde resin adhesives. These adhesives use formaldehyde as the main synthetic raw material, and have a high content of free formaldehyde. The prepared boards will continuously release formaldehyde, which is harmful to the environment and human health. In addition, the raw materials of these adhesives mainly come from petroleum resources. The non-renewable nature of petroleum resources and people's increasing attention to environmental issues and toxic volatile substances in adhesives have forced people to look for a renewable alternative that can prepare non-formaldehyde wood adhesives.

[0005] Lignin is a natural high molecular polymer with abundant reserves in nature. As a binder in the biosynthesis process of wood biomass, it can effectively bond cellulose and give cell walls and plants good strength and water resistance. Lignin is also the only biomass with aromatic groups in nature, but it can be biodegraded and is extremely environmentally friendly. These characteristics have attracted people's attention in the field of wood adhesives.

[0006] The Chinese invention patent with publication number CN105331325B discloses a lignin / polyurethane / polyethyleneimine wood adhesive and a preparation method thereof. The invention uses a lignin / polyurethane / polyethyleneimine adhesive prepared from demethylated modified lignin containing a catechol structure. The raw materials do not contain aldehydes, are green and environmentally friendly, and have high bonding strength and good water resistance. However, the demethylated modified lignin used in this method is in solid form, and an organic solvent needs to be used to dissolve it when preparing the adhesive, which is not only inconvenient to use, but also brings environmental problems.

[0007] The Chinese invention patent with publication number CN107987262B discloses a liquid polyester polyol containing lignin and an environmentally friendly polyurethane adhesive prepared using the same. The liquid polyester polyol containing lignin is prepared by lignin, catalyst A, diol, polyol and aliphatic dibasic acid, which can be used to replace polyols from petroleum resources and react with isocyanate to obtain an environmentally friendly polyurethane adhesive. However, after the liquid polyester polyol prepared by the invention contacts with isocyanate, it has a high reaction activity and can react quickly. Therefore, it is composed of a separately packaged component A and a separately packaged component B. When used, component A and component B are mixed to obtain a polyurethane adhesive. Since the adhesive has a short curing time and loses fluidity before sufficient penetration, thereby affecting the bonding effect, there are some problems in using it in the production of particleboard.

[0008] Therefore, the existing technology uses modified lignin to replace polyols from petroleum resources for the preparation of polyurethane adhesives, which are further applied to the preparation of particleboards. There are still some problems that need to be solved. Summary of the invention

[0009] The purpose of the present invention is to provide a low-density formaldehyde-free particleboard and a preparation process thereof in view of the above-mentioned problems. The present invention utilizes lignin from biomass and obtains a liquid polyester polyol by modifying it, which is used in the preparation of the particleboard core layer to obtain a formaldehyde-free lightweight particleboard with good mechanical properties. The preparation process does not contain organic solvents and is very environmentally friendly.

[0010] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0011] A preparation process of a low-density formaldehyde-free particleboard specifically comprises the following steps:

[0012] (1) Preparation of lignin-based liquid polyester polyol: by weight, 10 to 15 parts of chloroacetic acid, 6 to 10 parts of mixed small molecule diols, and 8 to 12 parts of methyl allyl alcohol are mixed under stirring; under the protection of inert gas, 30 to 40 parts of lignin, 2 to 4 parts of catalyst A, and 1 to 2 parts of antioxidant are added, and the temperature is raised to 155 to 165° C. for pre-reaction until the water output rate of the system reaches more than 95 wt % of the theoretical value, and then the temperature is raised to 190 to 200° C. and reacted for 2 to 3 hours; then the vacuum degree is adjusted to -0.06 MPa, and the reaction is carried out for 30 to 50 minutes, and the vacuum degree is continued to be adjusted to -0.08 MPa, and the reaction is carried out for 30 to 50 minutes, and the vacuum is stopped and the temperature is lowered to 40 to 50° C. to obtain a lignin-based liquid polyester polyol; the catalyst A is an organic titanium catalyst;

[0013] (2) Preparation of sizing solution: 120-150 parts by weight of lignin-based liquid polyester polyol, 30-40 parts by weight of G-15 liquid tackifying resin, 10-15 parts by weight of vinyl tri(β-methoxyethoxy)silane, 6-10 parts by weight of foaming agent, 3-4 parts by weight of catalyst B, and 160-200 parts by weight of water are mixed evenly, and then 180-230 parts by weight of isocyanate are added and mixed evenly to obtain sizing solution; the catalyst B is stannous octoate, dibutyltin dilaurate, monobutyltin oxide, or dibutyltin oxide;

[0014] (3) Gluing and paving wood chips: chipping, flaking, drying and screening the wood raw materials to obtain core chips, upper surface chips and lower surface chips with a moisture content of 2-4%; spraying the sizing solution obtained in step (2) on the chips respectively by using an atomizing glue sprayer, and infiltrating into the chips to obtain glued chips; the glue amount of the core chips is 8-10% of the mass of the core chips; the amount of sizing solution of the upper surface chips or the lower surface chips is 60%-80% of the amount of sizing solution of the core chips; paving the glued chips to obtain a slab;

[0015] (4) Pressing and forming: The slab is pre-pressed, hot-pressed, cooled, trimmed, and sanded to produce a low-density formaldehyde-free particleboard.

[0016] In the present invention, preferably, the lignin is corn straw lignin.

[0017] In the present invention, preferably, the mixed small molecule diol is one or more of 1,2-propylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propanediol, ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, and 1,5-pentanediol.

[0018] In the present invention, preferably, the foaming agent is cyclopentane, n-pentane or isopentane.

[0019] In the present invention, preferably, the isocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate, polymethylene polyphenyl isocyanate and diphenylmethane diisocyanate.

[0020] In the present invention, preferably, the pre-pressing conditions are: the pre-pressing temperature is 160-180° C., the pressure is maintained at 2.0-2.5 MPa for 1-2 min, and then the pressure is released to 0.5-0.8 MPa and maintained for 2-3 min.

[0021] In the present invention, preferably, the temperature of the hot pressing is 180-200° C., the pressure is maintained at 2.5-2.8 MPa for 0.5-1 min, and then the pressure is released to 0 MPa.

[0022] In the present invention, preferably, in the slab, the mass ratio of the lower surface layer, the core layer and the upper surface layer is 1:2.8 to 3.2:1.

[0023] In the present invention, preferably, the antioxidant is butylated hydroxytoluene or butylated hydroxyanisole.

[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0025] 1. The lignin-based liquid polyester polyol in the present invention is prepared by using lignin, chloroacetic acid, mixed small molecule diols and methyl allyl alcohol. During the research and development process, the ratio between the raw materials is controlled and the types of organic acids and alcohols are selected to change the arrangement of the molecular weight and affect its crystal state to obtain the liquid polyester polyol. At the same time, when the obtained polyol is used to replace the commercially available polyol for preparing polyurethane by polymerization with isocyanate, it can effectively inhibit the pre-reaction of -NCO at a temperature below 65°C, so that the adhesive system has a longer open time, and the adhesive can not be cured before pre-pressing and fully penetrate into the wood chips. During the hot pressing process, when the hot pressing temperature exceeds 70°C, -NCO can react with the polyol, the hydroxyl group, carboxyl group and other groups containing active hydrogen atoms on the surface of the wood chips to react faster, and a three-dimensional chemical cross-linked network structure is obtained to improve the satisfactory bonding effect. At the same time, the introduction of lignin can not only further improve the water resistance of the adhesive, but also the macromolecular rigid skeleton structure of lignin can give the polymer material good thermal stability and mechanical properties, thereby obtaining a particleboard with excellent comprehensive performance.

[0026] 2. The sizing solution of the present invention utilizes lignin-based liquid polyester polyols, thereby avoiding the use of organic solvents to dissolve solid polyols, reducing the use of organic solvents, and being more environmentally friendly. G-15 liquid tackifying resin and vinyl tri(β-methoxyethoxy)silane are added to the sizing solution to work together with the lignin-based liquid polyester polyols. The G-15 liquid tackifying resin has excellent fluidity and can improve the initial viscosity, peel strength and holding force of the system. Although there are many tackifying resin products on the market, some tackifying resins cannot be well soluble in the sizing solution system of the present invention, or have poor bonding performance with wood chips. The vinyl tri(β-methoxyethoxy)silane used in the sizing liquid reacts with the active functional group of lignin at one end and reacts with the hydroxyl group in the wood shavings at the other end to form a "bridge" connection, forming an inseparable bonding effect, so that the wood shavings are tightly combined; the lignin-based liquid polyester polyol reacts with isocyanate to have a certain foaming effect. In addition, a small amount of foaming agent is added to the sizing liquid, which can promote the flow of the adhesive so that it can fully fill the gaps between the wood shavings, promote the bonding between the wood shavings, and further improve the mechanical properties and water resistance of the board. The sizing liquid compound system obtained by the present invention can improve fluidity, wettability and adhesion, so that the adhesive is fully and evenly firmly combined with the wood shavings to form an ultra-stable bonding structure.

[0027] 3. In the pressing process of particleboard of the present invention, two steps of pre-pressing and hot pressing are carried out. During pre-pressing, the components of the sizing liquid begin to react, and the foaming agent begins to foam at the same time. After a short period of pre-pressing at a relatively high pressure, the slab is initially bonded and formed. Then the pressure is reduced to allow the internal reaction to proceed fully. The gas generated by the decomposition of the foaming agent prompts the sizing liquid system to quickly and fully fill the gaps between the wood chips, firmly combining the wood chips together. Finally, hot pressing is used to fully solidify and shape the evenly distributed sizing liquid, forming a uniform hard foam structure inside the particleboard, thereby obtaining a particleboard with low density and good mechanical strength.

[0028] 4. The preparation process of the present invention is free of organic solvents and uses degraded lignin-modified polyols instead of petroleum-derived polyols, which is very environmentally friendly. The prepared particleboard does not use formaldehyde-containing adhesives and has the characteristics of zero formaldehyde content, high bonding strength, good water resistance, and easy gluing. The bonding strength meets the bonding performance requirements of particleboard and the environmental protection requirements of household panels. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A preparation process of a low-density formaldehyde-free particleboard comprises the following steps:

[0032] (1) Preparation of lignin-based liquid polyester polyol: by weight, 10 parts of chloroacetic acid, 2 parts of 1,2-propylene glycol, 2 parts of 1,3-butanediol, 2 parts of 2-methyl-1,3-propanediol, and 8 parts of methyl allyl alcohol are mixed under stirring; under the protection of inert gas, 30 parts of corn straw lignin, 2 parts of tetraisopropyl titanate, and 1 part of antioxidant butylated hydroxytoluene are added, and the temperature is raised to 155° C. for pre-reaction until the water output rate of the system reaches more than 95wt% of the theoretical value, and then the temperature is raised to 190° C. and reacted for 3 hours; then the vacuum degree is adjusted to -0.06MPa, and the reaction is carried out for 30 minutes, and the vacuum degree is continuously adjusted to -0.08MPa, and the reaction is carried out for 30 minutes, and the vacuum is stopped and the temperature is lowered to 40° C. to obtain lignin-based liquid polyester polyol;

[0033] (2) Preparation of sizing solution: 120 parts by weight of lignin-based liquid polyester polyol, 30 parts of G-15 liquid tackifying resin, 10 parts of vinyl tri(β-methoxyethoxy)silane, 6 parts of cyclopentane, 3 parts of stannous octoate, and 160 parts of water were mixed evenly, and then 180 parts of isophorone diisocyanate was added and mixed evenly to obtain sizing solution;

[0034] (3) Gluing and paving wood chips: chipping, flaking, drying and screening the wood raw materials to obtain core chips, upper surface chips and lower surface chips with a moisture content of 2%; spraying the sizing solution obtained in step (2) on the chips respectively by using an atomizing glue sprayer, and infiltrating into the inside of the chips to obtain glued chips; the glue amount of the core chips is 8% of the mass of the core chips, and the amount of sizing solution of the upper surface chips and the lower surface chips is 60% of the amount of sizing solution of the core chips; paving the glued chips to obtain a slab, in which the mass ratio of the lower surface layer, the core layer and the upper surface layer is 1:2.8:1;

[0035] (4) Pressing and forming: The slab is pre-pressed at a pre-pressing temperature of 160°C, maintained at a pressure of 2.0 MPa for 2 min, and then the pressure is released to 0.5 MPa and maintained for 2 min; then hot-pressed at a temperature of 180°C, maintained at a pressure of 2.5 MPa for 1 min, and then the pressure is released to 0 MPa; after cooling, trimming, and sanding, a low-density formaldehyde-free particleboard is obtained.

[0036] Example 2

[0037] A preparation process of a low-density formaldehyde-free particleboard specifically comprises the following steps:

[0038] (1) Preparation of lignin-based liquid polyester polyol: 12 parts of chloroacetic acid, 4 parts of ethylene glycol, 4 parts of 1,3-propylene glycol, and 10 parts of methyl allyl alcohol were mixed under stirring; under the protection of inert gas, 35 parts of corn straw lignin, 3 parts of tetrabutyl titanate, and 1.5 parts of butyl hydroxyanisole were added, and the temperature was raised to 160° C. for pre-reaction until the water output rate of the system reached more than 95 wt % of the theoretical value, and then the temperature was raised to 195° C. and reacted for 2.5 hours; then the vacuum degree was adjusted to -0.06 MPa, and the reaction was carried out for 40 minutes, and the vacuum degree was continued to be adjusted to -0.08 MPa, and the reaction was carried out for 40 minutes, and the vacuum was stopped and the temperature was lowered to 45° C. to obtain lignin-based liquid polyester polyol;

[0039] (2) Preparation of sizing solution: 140 parts by weight of lignin-based liquid polyester polyol, 35 parts of G-15 liquid tackifying resin, 13 parts of vinyl tri(β-methoxyethoxy)silane, 3 parts of n-pentane, 5 parts of isopentane, 3.5 parts of dibutyltin dilaurate, and 180 parts of water were mixed evenly, and then 200 parts of hexamethylene diisocyanate were added and mixed evenly to obtain sizing solution;

[0040] (3) Gluing and paving wood chips: chipping, flaking, drying and screening the wood raw materials to obtain core chips, upper surface chips and lower surface chips with a moisture content of 3%; spraying the sizing solution obtained in step (2) on the chips by an atomizing glue sprayer and infiltrating into the chips to obtain glued chips; the glue amount of the core chips is 9% of the mass of the core chips, and the amount of sizing solution for the upper surface chips and the lower surface chips is 70% of the amount of sizing solution for the core chips; paving the glued chips to obtain a slab, in which the mass ratio of the lower surface layer, the core layer and the upper surface layer is 1:3:1;

[0041] (4) Pressing and forming: The slab is pre-pressed at a pre-pressing temperature of 170°C, maintained at a pressure of 2.3 MPa for 1.5 min, and then the pressure is released to 0.7 MPa and maintained for 2.5 min; then hot-pressed at a temperature of 190°C, maintained at a pressure of 2.7 MPa for 0.8 min, and then the pressure is released to 0 MPa; after cooling, trimming, and sanding, a low-density formaldehyde-free particleboard is obtained.

[0042] Example 3

[0043] A preparation process of a low-density formaldehyde-free particleboard specifically comprises the following steps:

[0044] (1) Preparation of lignin-based liquid polyester polyol: 15 parts of chloroacetic acid, 5 parts of 1,4-butanediol, 5 parts of 1,5-pentanediol, and 12 parts of methyl allyl alcohol were mixed under stirring; under the protection of inert gas, 40 parts of corn straw lignin, 4 parts of tetrabutyl titanate, and 2 parts of butyl hydroxyanisole were added, and the temperature was raised to 165° C. for pre-reaction until the water output rate of the system reached more than 95wt% of the theoretical value, and then the temperature was raised to 200° C. and reacted for 3 hours; then the vacuum degree was adjusted to -0.06MPa, and the reaction was carried out for 50 minutes, and the vacuum degree was continued to be adjusted to -0.08MPa, and the reaction was carried out for 50 minutes, and the vacuum was stopped and the temperature was lowered to 50° C. to obtain lignin-based liquid polyester polyol;

[0045] (2) Preparation of sizing solution: 150 parts by weight of lignin-based liquid polyester polyol, 40 parts by weight of G-15 liquid tackifying resin, 15 parts by weight of vinyl tri(β-methoxyethoxy)silane, 10 parts by weight of isopentane, 4 parts by weight of dibutyltin oxide, and 200 parts by weight of water were mixed evenly, and then 230 parts by weight of diphenylmethane diisocyanate were added and mixed evenly to obtain a sizing solution;

[0046] (3) Gluing and paving wood chips: chipping, flaking, drying and screening the wood raw materials to obtain core chips, upper surface chips and lower surface chips with a moisture content of 4%; spraying the sizing solution obtained in step (2) on the chips by an atomizing glue sprayer and penetrating into the chips to obtain glued chips; the glue amount of the core chips is 10% of the mass of the core chips, and the amount of sizing solution for the upper surface chips and the lower surface chips is 80% of the amount of sizing solution for the core chips; paving the glued chips to obtain a slab, in which the mass ratio of the lower surface layer, the core layer and the upper surface layer is 1:3.2:1;

[0047] (4) Pressing and forming: The slab is pre-pressed at a pre-pressing temperature of 180°C, maintained at a pressure of 2.5 MPa for 1 min, and then the pressure is released to 0.8 MPa and maintained for 2 min; then hot pressing is performed at a temperature of 200°C, maintained at a pressure of 2.8 MPa for 1 min, and then the pressure is released to 0 MPa; after cooling, trimming, and sanding, a low-density formaldehyde-free particleboard is obtained.

[0048] Comparative Example 1

[0049] The difference between this comparative example and Example 2 is that methyl allyl alcohol is replaced by an equal amount of neopentyl glycol. Other raw materials and preparation steps are the same as those in Example 2.

[0050] Comparative Example 2

[0051] The difference between this comparative example and Example 2 is that chloroacetic acid is replaced by an equal amount of succinic acid. Other raw materials and preparation steps are the same as those in Example 2.

[0052] Comparative Example 3

[0053] The difference between this comparative example and Example 2 is that when preparing the lignin-based liquid polyester polyol in step (1), 10 parts of chloroacetic acid, 6 parts of 1,2-propylene glycol, 6 parts of 1,3-butanediol, 2 parts of 2-methyl-1,3-propanediol and 2 parts of methyl allyl alcohol are mixed under stirring, by weight; the other raw materials and preparation steps are the same as those in Example 2.

[0054] Comparative Example 4

[0055] The difference between this comparative example and Example 2 is that the G-15 liquid tackifying resin in the sizing solution is replaced by an equal amount of hydrogenated C9 petroleum resin. The other raw materials and preparation steps are the same as those in Example 2.

[0056] The embodiment of the present invention and the comparative example both use eucalyptus wood shavings to make 18 mm particleboard; except for the corresponding raw material adjustment, the other process parameters of the embodiment and the comparative example are the same. According to the national standard (GB / T4897-2015 particleboard P2 type), the particleboards obtained in embodiment 2 and comparative examples 1-3 are tested for performance respectively. The density of the particleboard prepared in embodiment 2 is 428 kg / m 3 , the formaldehyde emission is 0, and other test results are shown in Table 1.

[0057] Table 1 Performance test results

[0058]

[0059] As can be seen from the above table, the particleboard prepared in the embodiment has excellent mechanical properties and waterproof properties, which fully meets the requirements of the national standard (GB / T4897-2015 particleboard P2 type). In the preparation of the particleboard in Comparative Examples 1 and 2, although the obtained lignin-based polyol is still in liquid state, the polyol fails to effectively inhibit the pre-reaction of -NCO at room temperature, the open time is short, and the sizing solution has no time to fully wet and penetrate the wood chips and solidify, resulting in poor final bonding effect, insufficient mechanical properties and waterproof properties of the product, and this sizing solution is not suitable for use in the production of particleboard. In the preparation of the particleboard of Comparative Example 3, when the ratio between chloroacetic acid, mixed small molecule diols, and methyl allyl alcohol changes, the obtained lignin-based polyol is a powdery solid, which is difficult to be evenly dispersed in isocyanate, and the final reaction is insufficient, affecting its mechanical properties and waterproof properties. The tackifying resin used in Comparative Example 4 has a poor bonding effect on wood chips, affecting the mechanical properties and waterproof properties of the particleboard.

[0060] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.

Claims

1. A process for preparing a low-density formaldehyde-free particleboard, characterized in that: The following steps are involved: (1) Preparation of lignin-based liquid polyester polyol: by weight, 10 to 15 parts of chloroacetic acid, 6 to 10 parts of mixed small molecule diols, and 8 to 12 parts of methyl allyl alcohol are mixed under stirring; under the protection of inert gas, 30 to 40 parts of lignin, 2 to 4 parts of catalyst A, and 1 to 2 parts of antioxidant are added, and the temperature is raised to 155 to 165° C. for pre-reaction until the water output rate of the system reaches more than 95 wt % of the theoretical value, and then the temperature is raised to 190 to 200° C. and reacted for 2 to 3 hours; then the vacuum degree is adjusted to -0.06 MPa, and the reaction is carried out for 30 to 50 minutes, and the vacuum degree is continued to be adjusted to -0.08 MPa, and the reaction is carried out for 30 to 50 minutes, and the vacuum is stopped and the temperature is lowered to 40 to 50° C. to obtain a lignin-based liquid polyester polyol; the catalyst A is an organic titanium catalyst; (2) Preparation of sizing solution: 120-150 parts by weight of lignin-based liquid polyester polyol, 30-40 parts by weight of G-15 liquid tackifying resin, 10-15 parts by weight of vinyl tri(β-methoxyethoxy)silane, 6-10 parts by weight of foaming agent, 3-4 parts by weight of catalyst B, and 160-200 parts by weight of water are mixed evenly, and then 180-230 parts by weight of isocyanate are added and mixed evenly to obtain sizing solution; the catalyst B is stannous octoate, dibutyltin dilaurate, monobutyltin oxide, or dibutyltin oxide; (3) Gluing and paving wood chips: chipping, flaking, drying and screening the wood raw materials to obtain core chips, upper surface chips and lower surface chips with a moisture content of 2-4%; spraying the sizing solution obtained in step (2) on the chips respectively by using an atomizing glue sprayer, and infiltrating into the chips to obtain glued chips; the glue amount of the core chips is 8-10% of the mass of the core chips; the amount of sizing solution of the upper surface chips or the lower surface chips is 60%-80% of the amount of sizing solution of the core chips; paving the glued chips to obtain a slab; (4) Pressing and forming: The slab is pre-pressed, hot-pressed, cooled, trimmed, and sanded to produce a low-density formaldehyde-free particleboard.

2. The preparation process according to claim 1, characterized in that: The lignin is corn straw lignin.

3. The preparation process according to claim 1, characterized in that: The mixed small molecule diol is one or more of 1,2-propylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propanediol, ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, and 1,5-pentanediol.

4. The preparation process according to claim 1, characterized in that: The foaming agent is cyclopentane, n-pentane or isopentane.

5. The preparation process according to claim 1, characterized in that: The isocyanate is one or more of isophorone diisocyanate, hexamethylene diisocyanate, hexamethylene diisocyanate, polymethylene polyphenyl isocyanate and diphenylmethane diisocyanate.

6. The preparation process according to claim 1, characterized in that: The pre-pressing conditions are as follows: the pre-pressing temperature is 160-180° C., the pressure is maintained at 2.0-2.5 MPa for 1-2 minutes, and then the pressure is released to 0.5-0.8 MPa and maintained for 2-3 minutes.

7. The preparation process according to claim 1, characterized in that: The temperature of the hot pressing is 180-200° C., the pressure is maintained at 2.5-2.8 MPa for 0.5-1 min, and then the pressure is released to 0 MPa.

8. The preparation process according to claim 1, characterized in that: In the slab, the mass ratio of the lower surface layer, the core layer and the upper surface layer is 1:2.8 to 3.2:

1.

9. The preparation process according to claim 1, characterized in that: The antioxidant is butylated hydroxytoluene or butylated hydroxyanisole.

10. The low-density formaldehyde-free particleboard prepared by the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A kind of lignin / polyurethane / polyethyleneimine wood adhesive and preparation method thereof

    CN105331325B

  • A lignin-containing liquid polyester polyol and an environmentally friendly polyurethane adhesive prepared therefrom

    CN107987262B

  • Polyester polyol containing lignin, preparing method thereof and polyurethane adhesive synthesized by same

    CN103665357A

  • Lignin / polyurethane / polyethyleneimine wood adhesive and preparation method thereof

    CN105331325A